(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: In forensic science, fibres are utilized to establish a link between the crime and the suspect. The samples are examined using several analytical methods to discover relationships between various clothing materials. The most typically studied forensic trace evidence in forensic laboratories are remnants of single fibres. The colour and dyes of fibre micro traces are studied using microscopic, chromatographic, and spectroscopic approaches, which play a significant part in forensic investigations. Objectives: This study aims to identify the forensic analysis of dyed textile fibres with various analytical techniques. Conclusion: Because of the significance of fibre clues in criminal investigation, a significant number of studies were done using analytical methods. Raman spectroscopy is being researched more and more for the forensic investigation of textile fibres, as it has a high potential for detecting and identifying dyes in fibres. In addition, FTIR can identify co-monomers, solvents and additives, allowing even more differentiation amongst acrylic fibre subclasses.